2009
DOI: 10.1016/j.jog.2009.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Natural and man-made induced hydrological signals, detected by high resolution tilt observations at the Geodynamic Observatory Moxa/Germany

Abstract: It is well known, that high resolution borehole tiltmeters are able to observe deformations, The correlated tilt effect is discussed regarding changes of the tilt amplitude and the orientation of the induced pendulum tip movement during the load phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…While the tilmeter in 30m depths clearly shows the periodic signal of the solid earth tides, the tilt record of the instruments near to the surface is dominated by large non-periodic signals hydrological, thermoelastic and barometric origin. Several investigations have shown that the site and the installation depths of tiltmeters has a major impact on environmental noise mainly coming from hydrology [41], [43], [44], [42] has shown that even in 100 m depths effects caused by hydrological changes are detectable, but strongly reduced in comparison to a 50 m deep installation. First investigations related to topographic and temperature induced effects were carried out by [39] and [40].…”
Section: Sensor Propertiesmentioning
confidence: 99%
“…While the tilmeter in 30m depths clearly shows the periodic signal of the solid earth tides, the tilt record of the instruments near to the surface is dominated by large non-periodic signals hydrological, thermoelastic and barometric origin. Several investigations have shown that the site and the installation depths of tiltmeters has a major impact on environmental noise mainly coming from hydrology [41], [43], [44], [42] has shown that even in 100 m depths effects caused by hydrological changes are detectable, but strongly reduced in comparison to a 50 m deep installation. First investigations related to topographic and temperature induced effects were carried out by [39] and [40].…”
Section: Sensor Propertiesmentioning
confidence: 99%
“…Many scientists have modeled the effects of land-water distribution on the observed gravity (e.g., Francis et al, 2004;Abe et al, 2006;Boy and Hinderer, 2006;Meurers et al, 2007;Jahr et al, 2009;LeiriĂŁo et al, 2009;Longuevergne et al, 2009;Nawa et al, 2009;Pfeffer et al, 2011). For example, Hanada et al (1990) found a simple proportional relationship between water level and abCopyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, relative deformation instruments like tiltmeters and strainmeters were introduced in an innovative way to apprehend both short‐ and long‐term subsurface flow phenomena, first in volcanology where the signal is strong due to large inflating cavities [ Dzurisin , ] and later in hydrogeology thanks to technical improvement of these instruments [ Boudin et al , ; Hisz et al , ]. In particular, much effort has been dedicated into assessing how they can be used to characterize properties of groundwater flow, whether fluxes are man driven [ Chen et al , ; Barbour and Wyatt , ; Fabian and KĂŒmpel , ] or natural [ Braitenberg , ; Jahr et al , ]. Furthermore, tiltmeters are very efficient when it comes to capture transient responses to subsurface progressive pressure variation, which is a convenient way to spot productive zones without having the need for supplementary boreholes [ Vasco et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Well F30, located at a few hundreds of meters west from the pumping site, was used as the nonmoving reference point for the least squares adjustment of the optical leveling data. are man driven [Chen et al, 2010;Barbour and Wyatt, 2014;Fabian and KĂŒmpel, 2003] or natural [Braitenberg, 1999;Jahr et al, 2009]. Furthermore, tiltmeters are very efficient when it comes to capture transient responses to subsurface progressive pressure variation, which is a convenient way to spot productive zones without having the need for supplementary boreholes [Vasco et al, 2001].…”
Section: Introductionmentioning
confidence: 99%